Genome sequence and description of Traorella massiliensis gen. nov., sp. nov., a new bacterial genus isolated from human left colon. (May 2019) - Bonnet, M.; Mailhe, M.; Ricaboni, D.; Labas, N.; Richez, M.; Vitton, V.; Benezech, A.; Fournier, P.-E.; Million, M.; Raoult, D.; Khelaifia, S.
Abstract: A strictly anaerobic, motile, non–spore-forming, Gram-negative, rod-shaped bacterium designated Marseille-P3110 T was isolated from the left colon cleansing of a 76-year-old Frenchwoman. Its 16S ribosomal RNA (rRNA) gene showed a 93.2% similarity level with the 16S rRNA of Dielma fastidiosa strain JC13, the closest species with a validly published name. The genome of Marseille-P3110 T is 2 607 061 bp long with 35.99% G+C content. Of the 2642 predicted genes, 2582 were protein-coding genes and 60 were RNAs, including five 16S rRNA genes.